NAVIGATING INSTABILITY: ADAPTIVE STRATEGIES OF MALAYSIAN CONSTRUCTION FIRMS IN TIMES OF CRISIS - Zainon, Nurshuhada; Aziz, Nur Mardhiyah; Loo Siaw Chuing (Journal of Surveying, Construction and Property, 2025)
The construction industry is highly vulnerable to macroeconomic fluctuations, with its performance closely linked to national indicators such as Gross Domestic Product (GDP). This study aims to identify effective survival strategies that enable construction firms in Malaysia to withstand periods of economic downturn. Specifically, the research investigates the key factors contributing to economic crises, examines their impacts on construction firms and formulates practical strategies to support contractors during recessionary conditions. A quantitative research design was adopted, utilising an online questionnaire distributed to 450 construction firms’ grades G1-G7, registered with the Construction Industry Development Board (CIDB) Malaysia. The response rate yielded approximately 30.4%. The data were analysed using descriptive statistics, including mean and the Relative Importance Index (RII) to establish the prioritisation of contributing factors, impacts and survival strategies. The analysis identified nine critical strategies that offered a structured and actionable framework for firms seeking to enhance resilience during economic disruptions. Among the strategies are strengthening client relationships, enhancing financial management, improving operational efficiency, and diversifying markets to support business continuity. The findings provide valuable insights for industry practitioners and policymakers by highlighting the major economic pressures faced by construction firms and presenting strategic measures to mitigate the adverse effects of future economic crises.